Cyclophosphamide for the treatment of Acute Exacerbation of Interstitial Lung Disease: A Review of the Literature: Cyclophosphamide and Interstitial Lung Disease - Innabi, Ayoub; Gomez-Manjarres , Diana; Alzghoul , Bashar; Chizinga, Mwelwa; Mehrad, Borna; Patel, Divya (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Acute exacerbation of interstitial lung disease is a serious and life-threatening event. However, little is known about treatment options. Cyclophosphamide has been proposed in randomized clinic trials as a treatment option in progressive cases of scleroderma related interstitial lung disease. However, in acute exacerbation of interstitial lung disease, we found only small case series, and retrospective studies, mostly with no comparative groups which described the role of cyclophosphamide. Results of these studies showed mixed outcome, with no robust evidence that cyclophosphamide adds any benefit in treating acute exacerbations of interstitial lung disease. More well-designed studies including randomized clinical trials are needed to better understand the role of cyclophosphamide during exacerbations of ILD. In this review article we summarize the current evidence on the use of cyclophosphamide in interstitial lung disease with a focus on the acute exacerbation events.